2016
DOI: 10.21273/horttech.26.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Potassium Fertilization on Fruit Growth Rate, Potassium Accumulation, Yield, and Quality of ‘Kousui’ Japanese Pear

Abstract: A field experiment was conducted over three growing seasons (2012–14) to study the effect of the foliar application of different potassium (K) fertilizers [potassium phosphate monobasic (KH2PO4), potassium nitrate (KNO3), and humic acid potassium (HAK)] on the fruit growth rate, yield, and quality of ‘Kousui’ japanese pear (Pyrus pyrifola) trees. Except the first year of study, foliar application of K fertilizers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Spraying of pear trees with sodium selenate (Na 2 SeO 4 ) resulted in a significant increase in the total soluble solids content of the fruits ( Pezzarossa et al, 2012 ). In addition, foliar applications with KNO 3 can enhance fructose and sucrose content, as was observed in ‘Kousui’ Japanese pears ( Pyrus pyrifola ) ( Shen et al, 2016 ). Therefore, we also included a combination treatment consisting of I with Na 2 SeO 4 and KNO 3 in our field experiments.…”
Section: Introductionmentioning
confidence: 64%
“…Spraying of pear trees with sodium selenate (Na 2 SeO 4 ) resulted in a significant increase in the total soluble solids content of the fruits ( Pezzarossa et al, 2012 ). In addition, foliar applications with KNO 3 can enhance fructose and sucrose content, as was observed in ‘Kousui’ Japanese pears ( Pyrus pyrifola ) ( Shen et al, 2016 ). Therefore, we also included a combination treatment consisting of I with Na 2 SeO 4 and KNO 3 in our field experiments.…”
Section: Introductionmentioning
confidence: 64%
“…In our previous research, we found that pear fruit size sharply increased from the enlargement stage to maturity (Shen et al, 2016 ). A large number of mineral elements and carbohydrates are needed in fruits in the later stages of their development (data unpublished).…”
Section: Introductionmentioning
confidence: 84%
“…In terms of quality, the fruits were comparable to the ones obtained at the Warszawa-Wilanów station, but worse in comparison to the crop from the Ursynów station [Pitera et al 2009]. In other experiments, mean weight of fruits of Asian cultivars was much higher, in many cases exceeding 200 g, or even 300 g [Faoro and Nakasu 2002, Reighard et al 2008, Faoro and Orth 2010, Sakamoto et al 2016, Shen et al 2016. Such large fruits can be obtained only in regions characterized by the optimal climate, i.e.…”
Section: Resultsmentioning
confidence: 73%
“…Similar results were obtained by Faoro and Orth [2010] and Sakamoto et al [2016] with regard to the 'Kosui', 'Hosui', and 'Nijisseiki' cvs. Soluble sugar content in fruits from other research centers was both lower (the cultivars: 'Chojuro', 'Nijisseiki', 'Kosui, 'Hosui', 'Shinseiki' [Chen et al 1987, McArtney and Wells 1995, Larsen et al 2013, Shen et al 2016) and higher ('Nijisseiki', 'Shinseiki', 'Chojuro' [Chen et al 1987, Kopera and Mitek 2003). In the presented study, the fruits of 'Chojuro', 'Hosui', and 'Shu Li' had more polyphenols, whereas 'Kosui', 'Shinseiki', and 'Nijisseiki' -more phosphorus than pears collected from 'Conference'.…”
Section: Resultsmentioning
confidence: 99%